STRATEGI PONDOK PESANTREN DALAM PEMBELAJARAKELAS III ULYA (STUDI KASUS PONDOK PESANTREN MANBAUL ISHLAH LABUHAN MARINGGAI) - Nursamsiyah (ISLAMIDA Journal of Islamic Studies, 2023)
Pesantren is a traditional education in which students live together and study under the guidance of teachers who are better known as kiai and have dormitories for students to stay. There are two types of santri in a pesantren, namely, mukim students and bat students. Santri mukim are students who sleep and stay at the boarding school while studying at the boarding school, while santri bats are students who only take part in the Koran at the Islamic boarding school but return to their parents' homes, usually the bat students leave in the afternoon and return home at night after finishing the Koran or in the morning. Learning is an activity / activity that a person does consciously or intentionally. There are several learning methods that are generally used in the Manbaul ishlah Islamic boarding school, the Sorogan method, the wetonan/bandongan method, the bahtsul masail/deliberation method, the muhafadoh (memorization) method, the market recitation method and the demonstration method. Based on the subject matter studied, namely the Wetonan/bandongan learning process at the Manbaul Ishlah Islamic Boarding School, Labuhan Maringgai, East Lampung. Then this type of reseach is a qualitative research because it describes systematically, factually, and accurately about the facts and characteristics of the population in the Manbaul Ishlah Islamic boarding school Labuhan Maringgai, East Lampung. That way we can conclude that in the Manbaul Ishlah Islamic boarding school, Labuhan Maringgai, East Lampung, the wetonan/bandongan learning method is used because it is more effective and efficient. Although they still use the wetonan/bandongan method which is usually considered old school, but with this method it can be faster to finish the books taught at the Manbaul Ishlah Islamic Boarding School